2021
DOI: 10.3389/fonc.2020.566183
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Analysis of CDCAs Methylation and Immune Infiltrates in Hepatocellular Carcinoma

Abstract: BackgroundAs essential components of cycle growth, the cell division cycle-associated family genes (CDCAs) have crucial roles in tumor development and progression, especially in hepatocellular carcinoma (HCC). However, due to the tumor heterogeneity of HCC, little is known about the methylation variability of CDCAs in mediating phenotypic changes (e.g., immune infiltrates) in HCC. Presently, we aim to comprehensively explore the expression and prognosis of CDCAs methylation with regard to immune infiltrates of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 62 publications
1
10
0
Order By: Relevance
“…Notably, some studies have illuminated that CDCAs were associated with immune infiltration. Wang et al (28) suggested that CDCAs show a powerful association with immune function regulation in hepatocellular carcinoma (HCC). Wu et al (29) also indicated that CDCAs' expression was correlated with the abundance of immune infiltrates in head and neck squamous cell carcinoma (HNSCC).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, some studies have illuminated that CDCAs were associated with immune infiltration. Wang et al (28) suggested that CDCAs show a powerful association with immune function regulation in hepatocellular carcinoma (HCC). Wu et al (29) also indicated that CDCAs' expression was correlated with the abundance of immune infiltrates in head and neck squamous cell carcinoma (HNSCC).…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al. ( 28 ) suggested that CDCAs show a powerful association with immune function regulation in hepatocellular carcinoma (HCC). Wu et al.…”
Section: Introductionmentioning
confidence: 99%
“…Another study identified a broad DNA methylation signature in peripheral blood mononuclear cells and T cells of HCC patients that differed from that of non-HCC patients (89). Additionally, differences in immune infiltrates related to the methylation levels of cell division cycle-associated (CDCA) family genes in HCC were reported to have potential as predictive biomarkers for responses to immunotherapy (90). Notably, Llopiz et al reported that an epigenetic drug/ICI combination exerted synergistic antitumor effects in a murine model of HCC (91), thereby providing further evidence that DNA methylation signatures may be related to the efficacy of immunotherapy, and also have the potential to serve as biomarkers of combination therapy.…”
Section: Specific Gene Alterationsmentioning
confidence: 99%
“…Another study identified a broad DNA methylation signature in peripheral blood mononuclear cells and T cells of HCC patients that differed from that of non-HCC patients ( 89 ). Additionally, differences in immune infiltrates related to the methylation levels of cell division cycle-associated (CDCA) family genes in HCC were reported to have potential as predictive biomarkers for responses to immunotherapy ( 90 ). Notably, Llopiz et al.…”
Section: Potential Predictive Biomarkers For Ici-based Treatmentmentioning
confidence: 99%
“…The prognostic values of CDCAs are well documented in several cancers, including ovarian cancer, hepatocellular carcinoma, and endometrial carcinoma [ 19 - 21 ]. However, the function and prognostic utility of the CDCA family in GC, especially stomach adenocarcinoma (STAD), remain unknown and elusive.…”
Section: Introductionmentioning
confidence: 99%